Lagoas do Norte PI: satisfação residencial e significados do reassentamento - Nunes, Celso Roberto (2010)
The work consists of a psychosocial study of the meanings of technical and resettlement for relocated families and an assessment of the residential satisfaction of these families, from a case study: the Residential Zilda Arns in Teresina, Piauí. This is a qualitative study used semi-structured interviews, which was performed content analysis by computer program NUD-IST and had its analysis and interpretation 15 families resettled, 4 technicians, equivalent to 5% and 50% respectively. The study it indicated that the joined meanings had turned around terms such as: in a social constructionist view of the critical and environmental psychology based largely on Lincoln (1994), Ibáñez (1994), Scott (2006), Amérigo (1995) and Wiesenfeld (1997), since these approaches allow us to understand the power relations and exploitation found among the actors involved, the follows: solution, output, need, requirement and satisfaction. The study also showed that the resettlement process represented a gain for professional technicians and improvement of housing conditions for families affected, but put them in vulnerable situations causing a high psychological cost. We observed an overall satisfaction level is high, especially in the components meet with neighbors and with the locality (supported by CAPES)